PENGGUNAAN KOMBINASI GROSS ENERGY DAN PROTEINTERHADAP KONSUMSI PAKAN DAN PERKEMBANGAN BOBOT BADAN ULAT HONGKONG - Eka Fitasari; Erik Priyo Santoso (Universitas Tribhuwana Tunggadewi, 2015)
Fisheries and lovebirdcommodity, and cosmetics causing mealworm become popular to find and having purpose as source cosmetics mixing and source of feed. Because of many source of feed in market, people or researcher should pay attention on nutrition need of each animal, energy and protein become principal references for production increasing. This research was done to know the influence of the using gross energy (GE) and crude protein (CP) combination and also looking for the best combinationthat giving good result on feed consumption and body weight gain of mealworm. This research used Factorial experiment in Completetely Randomized Design with 9 treatments were G1P1 (GE 4000 kkal/kg , CP 10%), G1P2 (GE 4000 kkal/kg , CP 12%), G1P3 (GE 4000 kkal/kg , CP 14%), G2P1 (GE 4500 kkal/kg , CP 10%), G2P2 (GE 4500 kkal/kg , CP 12%), G2P3 (GE 4500 kkal/kg, CP 14%), G3P1(GE 5000 kkal/kg,CP 10%) G3P2 (GE 5000 kkal/kg,CP 12%), G3P3 (GE 5000 kkal/kg,CP 14%).From the research can be concluded that the using of feed gross energy and crude protein combination doesn’t give significant effect e on feed consumption, body weight gain, feed convertion/FCR, and body length. 12% and 14% protein combination with 4500 and 5000 kkal/kg gross energy cousing highes mortality on mealworm live. It is suggested to use feed with maximum nutrition content 4500 kkal/kg GE and 12% protein for getting feed efficiency and looking for another source for changing oil as energy source.